Storytelling with data : a data visualization guide for business professionals - Knaflic, Cole Nussbaumer (Hoboken, New Jersey : Wiley, 2015)
Sometimes it is easy to generate charts and graphs look fine to you, but don't clearly communicate the information that they represent. Knaflic's own knack for clarity will help you sharpen your message when using data in your business presentations
The importance of context -- Choosing an effective visual -- Clutter is your enemy! -- Focus your audience's attention -- Think like a designer -- Dissecting model visuals -- Lessons in storytelling -- Pulling it all together -- Case studies -- Final thoughts
Includes bibliographical references and index
Keywords: Information visualization; Business communication; Computer graphics; Business presentations